Hubungan Kebisingan Rumah dengan Kejadian Hipertensi - Wahyu Sandika Putra; Farida Heriyani; Djallalluddin Djallalluddin (Homeostasis, 2020)
Abstract: The rate of high population density and dense residential houses in East Kelayan Health Center Region, Banjarmasin can trigger some disturbing noises. These noises may result to the increase levels of stress hormones such epinephrine, non-epinephrine and cortisol, which can lead to hypertension. This study aims to determine the association between house noise and the occurence of hypertension in dense residential houses at East Kelayan Health Center Region, Banjarmasin. This study used an analytic observational method with a case control approach. The sample of this study were patients with hypertension and non-hypertension based on medical record data according to the diagnosis by the doctors at East Kelayan Health Center from January-July 2019. The sample were obtained using simple random sampling technique. Chi-square test is used to analyze the data. The results in the case group showed there are 86.7% of patients with hypertension in noisy areas, and 13.3% in quite áreas. The results of the control group showed there are 53.3% of patients without hypertension in noisy areas, and 46.7% in quite areas. Chi square analysis showed the result of (p = 0.011 OR = 5.688) showing there is a significant association between house noise and the occurence of hypertension in dense residential houses at East Kelayan Health Center Region Banjarmasin. Keywords: Noise homes, hypertension, solid occupancy, East Kelayan. Abstrak: Kepadatan penduduk yang tinggi dan hunian rumah yang padat di wilayah Puskesmas Kelayan Timur Banjarmasin dapat memicu suatu kebisingan di wilayah tersebut. Akibat dari kebisingan tersebut dapat meningkatkan kadar hormon stres, seperti epineprin, non-epinerpin dan kortisol tubuh yang dapat mengakibatkan terjadinya hipertensi. Tujuan penelitian ini untuk mengetahui hubungan kebisingan rumah dengan kejadian hipertensi pada hunian rumah yang padat di wilayah Puskesmas Kelayan Timur Banjarmasin. Penelitian ini menggunakan metode observasional analitik dengan pendekatan case control. Sampel penelitian ini pasien hipertensi dan tidak hipertensi berdasarkan data rekam medis yang sesuai diagnosis dokter Puskesmas Kelayan Timur Banjarmasin periode Januari-Juli 2019. sampel diambil menggunakan simple random sampling. Uji análisis dengan chi-square. Hasil penelitian ini pada kelompok kasus terdapat 86,7% penderita hipertensi berada di tempat yang bising, 13,3% tidak bising sedangkan kelompok kontrol terdapat 53,3% penderita tidak hipertensi berada di tempat yang bising, 46,7% tidak bising. Hasil análisis dperoleh (p=0,011 OR=5,688) terdapat hubungan yang signifikan antara kebisingan rumah dengan kejadian hipertensi pada hunian rumah yang padat di wilayah Puskesmas Kelayan Timur Banjarmasin. Kata-kata kunci: Kebisingan rumah, hipertensi, hunian padat, Kelayan Timur.